Gastrodiplomasi Sebagai Media Branding Wisata Kuliner Nusantara - Untari, Dhian Tyas (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Culinary is a motivational factor that encourages individual action in a particular community or entire society. On the other hand, culinary is also part of the life cycle pattern. Culinary can be said to be a bond between one community and another. With the enormous potential of Indonesia's culinary wealth, it can be developed into an opportunity for media branding Indonesia to the world community, building awareness and understanding of the world community towards Indonesia through the development of culinary tourism, where we know that tourism and culinary are a mutual combination. . This research is a literature review which is a collection of reference theories that form the basis of research. The aim is to theoretically answer problems related to how gastrodiplomacy can be developed as a branding medium for culinary tourism in Indonesia.